Uslub al-Fi’l al-Mudhari’ fi Khutbah al-Jum’ah li al-Syaikh Abd al-Majid ibn Abd al-Hamid - Hamdy, Mohammad Zainal; Masdur, Masdur (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2022)
The Friday sermon in terms of legal terminology is (the sermon delivered on the pulpits on Friday with the intention of encouraging people to do good, encouraging them to do it, distracting them from evil and its motives, and making them aware of their conditions and the reality of their affairs, as required by the law. In this research, the researcher presented an important matter, which is the method of expressing the present tense verb in the Friday sermon of Sheikh Abdul Majeed bin Abdul Hamid, and the research method of this research is some of the types of library research. types of books. After the researcher looked at the Friday sermon, he found twenty-two in it, which consisted of 8 present tense parsing with a pronounced vowel, and from 1 parsing of the present tense with a vowel estimated in a thousand, and from 1 parsing of the present tense with a vowel estimated by wu, and from 10 parsing of the present tense verb with a vowel, And from 1 the parsing of the present verb is compounded by the sukoon estimated by a thousand, and from 1 the expression of the present tense verb is compounded by the sukoon estimated by ya. And from 2 the articulation of the present verb if it is called by a nominative plural pronoun, and from 1 the articulation of the present verb if it is called by a plural pronoun that is plural.